The determinants of female labor force participation for OECD countries - ALTAŞ KARACA, DİLEK; ÜN, TURGUT (My University, 2016)
Female labor force participation rate for women aged between 25 and 54 has increased from 54 percent in 1980 to 61 percent in 2013 in OECD countries. The reasons for this increase could be investigated by looking at the factors affecting labor demand and supply. Labor demand is mainly determined by the increase in production, the development of part-time and public sector employment. Whereas the factors affecting labor supply are considered as the increase in female educational attainment, postponement of fertility and the change in the attitude of female employment. Also economic, cultural and sociological issues are the factors affecting female labor force participation in the OECD countries. The aim of this paper is to analyze the determinants of female labor force participation in OECD countries which are per capita GDP, unemployment rate, ratio of female to male tertiary enrollment, fertility rate and the number of waged and salaried workers using panel logit model. The data is obtained from World Bank database and covers the period between 1990 and 2013. It is found that unemployment rate, gross domestic product per capita and fertility rate are affecting the female labor force participation rate positively and significantly. Fertility rate is found to be the variable with the highest effect on female labor force participation rate.
Keywords: Female labor force participation rate; panel logit model; OECD countries; unemployment rate; fertility rate